Tax Understanding, Morality, and Compliance: The Moderating Role of Tax Awareness in Jakarta's Delivery Service Companies - Indri Muktiasih; Lin Oktris (Journal of Social Research, 2025)
This study examines the effects of tax understanding and taxpayer morality on tax compliance moderated by tax awareness. Tax compliance is very important to ensure that the government obtains sufficient state revenue. Factors that influence compliance, such as tax understanding, taxpayer morality, and tax compliance have been widely conducted, but research influenced by tax awareness as a moderator variable has not been widely conducted. Tax understanding can help taxpayers fulfill their obligations, while taxpayer morality is related to ethical beliefs that drive compliance. Tax awareness involves individuals' recognition of their tax responsibilities. This quantitative study used a survey approach, collecting data through questionnaires from 103 corporate taxpayers in a shipping service company in Jakarta. Data were analyzed using the Partial Least Squares (PLS) method. Tax understanding has a positive impact on tax compliance, while taxpayer morality has no significant effect. Tax awareness weakens the relationship between tax understanding and compliance but does not significantly moderate the impact of taxpayer morality on compliance. In addition, tax awareness negatively affects compliance, because taxpayers who are more aware can be critical of the tax system. As a result of this study, taxpayers with better tax understanding are more compliant. Taxpayer morality alone is not enough to drive compliance, with factors such as understanding and awareness playing a more dominant role. While tax awareness moderates the effect of tax understanding on compliance, it does not moderate the effect of taxpayer morality. High awareness can lead to greater criticism of the tax system, reducing compliance.